Ocean tides trigger ice shelf rift growth and calving - O. J. Marsh; R. J. Arthern; J. De Rydt (Nature Communications)
Abstract Tabular iceberg calving reduces ice-shelf extent, affecting ocean circulation and ice-sheet stability. Here we present detailed observations of a rift on the Brunt Ice Shelf, East Antarctica, from 2017-2023 and its behaviour in the lead up to calving in January 2023. The timing of rift propagation was controlled by the rate of change of ocean tide height, wind speed, and an iceberg collision in August 2021, as well as the long-term ice dynamics. A viscoelastic rheological model is used to estimate the relative magnitude of stresses acting on the rift and to determine a critical threshold for fracture, which was exceeded during a sequence of propagation events in early 2019. The eventual calving on 22nd January 2023 occurred at the peak of a spring tide, supporting the conclusion that tides directly influenced the timing.